Study on the thermal oxidative stabilization reactions and the formed structures in polyacrylonitrile during thermal treatment. (June 2017) - Fu, Zhongyu; Liu, Baijun; Sun, Lihao; Zhang, Huixuan
Abstract: The structural evolution of polyacrylonitrile (PAN) homopolymer during thermal oxidative stabilization (TOS) was tracked quantitatively by using fourier transform infrared spectroscopy (FTIR) and curve-fitting technology. The cyclization, dehydrogenation of linear PAN macromolecule chains, oxygen uptake reactions of linear PAN macromolecule chains and cyclic structures were discussed in detail through tracking quantitatively the evolution of some specific groups. The cyclization, dehydrogenation and oxygen uptake reactions were evolved synchronously at the initial stage of TOS processes, but dehydrogenation and oxygen uptake reactions became dominant as cyclization extent above 0.7. Based on the data from FTIR and curve-fitting, a new procedure was developed to calculate the formed cyclic structures. The cyclic structures formed at 250 °C possessed length about seven successive aromatic rings; however, the cyclic structures formed at 265 °C possessed length about six successive aromatic rings. The graphite-like structures of the carbonized PAN films which were stabilized at 250 °C possessed were better than that of the carbonized PAN films which were stabilized at 265 °C.